Implementation of KLEMS Economic Productivity Accounts in Poland - Kotlewski, Dariusz Cezary; Błażej, Mirosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The aim of the article is to demonstrate how the KLEMS economic productivity accounts for Poland have been performed. The main research problem was to find solutions to certain country‑specific data insufficiencies. On this basis, a hypothesis was put forward that by using some innovative but acceptable missing data assessment techniques, it is possible to supply sufficient data for Poland for the mentioned accounts. After an overview of KLEMS economic productivity accounts and the relevant fundamental methodology, the article presents further how specific data problems that have arisen have been solved.